1999
DOI: 10.1002/(sici)1520-6629(199907)27:4<367::aid-jcop1>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' exposure to community violence: Sleep and psychophysiological functioning

Abstract: The relationships among psychophysiological indices, sleep disturbance, and adolescents' exposure to community violence were examined in a pilot study of 64 community youth (ages 16–18; 84% African American), 25 of whom had their blood pressure and pulse rates assessed. Neither age nor gender differences were found in self‐reported sleep disturbance or community violence exposure. Self‐reported exposure to community violence and sleep deprivation were positively related. Multivariate analyses of covariance (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
36
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 15 publications
10
36
1
Order By: Relevance
“…The only known study to examine psychophysiological responses in a sample of individuals exposed to community violence provides support for the notion that psychophysiological activity may change as a result of violence exposure (Cooley-Quille & Lorion, 1999). In this pilot study, urban adolescents categorized as high on violence exposure showed lower resting HR and systolic blood pressure relative to those with low exposure.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…The only known study to examine psychophysiological responses in a sample of individuals exposed to community violence provides support for the notion that psychophysiological activity may change as a result of violence exposure (Cooley-Quille & Lorion, 1999). In this pilot study, urban adolescents categorized as high on violence exposure showed lower resting HR and systolic blood pressure relative to those with low exposure.…”
contrasting
confidence: 99%
“…This hypothesis was not supported in that, even though cortisol, HR, and HRV were related to aggression, none of these measures differed between the high-and low-exposed groups. This finding is in contrast to the pilot study by Cooley-Quille and Lorion (1999) who found low resting-pulse rates in 16-to 18-year-old urban youth at the highest of three levels of violence exposure. It is possible that such group differences will only emerge in high-risk samples where violence exposure is more severe, pervasive, or recent.…”
Section: The Mediating Role Of Psychophysiological Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported links between community violence exposure and symptoms of posttraumatic stress disorder (Berman et al, 1996;Fitzpatrick & Boldizar, 1993;Garbarino, Kostelny, & Dubrow, 1992;Horowitz, Weine, & Jekel, 1995;Kliewer, Lepore, Oskin, & Johnson, 1998), aggressive and delinquent behaviors (Attar, Guerra, & Tolan, 1994;DuRant, Pendergrast, & Cadenhead, 1994a;Gorman-Smith & Tolan, 1998;Miller, Wasserman, Neugenbauer, Gorman-Smith, & Kamboukos, 1999;Schwab-Stone et al, 1995), heightened anxiety and depression (Freeman, Mokros, & Poznanski, 1993;Kliewer et al, 1998), unusually pronounced grief and loss reactions (Freeman, Schaffer, & Smith, 1996;Osofsky et al, 1993;Pynoos & Eth, 1985), increased recklessness in play (Schwab-Stone et al, 1995), sleep disturbances (Cooley-Quille & Lorion, 1999) and cognitive or academic delays (Osofsky et al, 1993;Shakoor & Chalmers, 1991). Such an expanding array of findings has heightened recognition that community violence exposure among children and youths is a large-scale problem with often profound consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Findings obtained by Scarpa, Fiktoglu, and Luscher (in press) support preliminary evidence reported by Cooley-Quille and Lorion (1999) that exposure to violence in one's surroundings is associated with physiological indices of stress, arousal and, we suspect, sleep disorders. Albeit only minimally studied to date, it appears that sleep-related disorders are reported disproportionately in those reporting high levels of exposure to pervasive violence.…”
mentioning
confidence: 99%